On one extremal problem of Pompeiu sets - Elets, L. V.; Masharov, P. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We determine upper bounds for the least radius of a ball in which a given set is a Pompeiu set (the set considered is a half right circular cone). The obtained estimates significantly improve known results.